2006
DOI: 10.1007/bf03022258
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of patients receiving vitamin K antagonists

Abstract: Purpose: As the number of patients taking vitamin K antagonists (VKA) is growing, the clinician is increasingly faced with having to make decisions regarding anticoagulation therapy before, during and immediately after surgery. In this article we review the indications for VKA and assess their use in the perioperative period based on available pharmacological and clinical data.Source: An on-line computerized search of Medline was conducted limited to English and French language articles. The bibliographies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
11
0
2
Order By: Relevance
“…In general, however, the periprocedural antithrombotic treatment appears to have been carried out in our population according to the current recommendations for patients on VKA treatment undergoing invasive procedures [8][9][10][11], although some variability within same classes of indication was observed ( Table 2). This finding may be accounted for by the heterogeneous thromboembolic risk profile of patients with atrial fibrillation, in whom in fact, the highest treatment variability was observed ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In general, however, the periprocedural antithrombotic treatment appears to have been carried out in our population according to the current recommendations for patients on VKA treatment undergoing invasive procedures [8][9][10][11], although some variability within same classes of indication was observed ( Table 2). This finding may be accounted for by the heterogeneous thromboembolic risk profile of patients with atrial fibrillation, in whom in fact, the highest treatment variability was observed ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…The available information on the periprocedural treatment mostly derives from small studies [4][5][6][7] or practice guidelines [8][9][10][11] and overviews [12] on the management of patients receiving vitamin K antagonists (VKA) undergoing invasive procedures in general (i.e. surgery, dental extraction, endoscopic examination or treatment, pacemaker implantation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…‘Bridging therapy’ is the administration of an appropriate form of heparin while the oral anticoagulation is discontinued. In recent years, bridging has been procured mainly using LMWH, and only occasionally with intravenous UFH14, 18–20, 29. LMWH is started once the INR is less than 2·0 after the cessation of warfarin.…”
Section: Preoperative Periodmentioning
confidence: 99%
“…Other adverse effects are nausea, diarrhoea and anaemia. Also worth mentioning is skin necrosis at the initiation of therapy due to the rapid decrease in protein C and S initiating a hypercoagulable state and formation of thrombi in subcutaneous fat 8 …”
Section: Characteristics Of Vitamin K Antagonistsmentioning
confidence: 99%